2015
DOI: 10.1111/ppl.12385
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid‐induced gene expression in the liverwort Marchantia polymorpha is mediated by evolutionarily conserved promoter elements

Abstract: Abscisic acid (ABA) is a phytohormone widely distributed among members of the land plant lineage (Embryophyta), regulating dormancy, stomata closure and tolerance to environmental stresses. In angiosperms (Magnoliophyta), ABA-induced gene expression is mediated by promoter elements such as the G-box-like ACGT-core motifs recognized by bZIP transcription factors. In contrast, the mode of regulation by ABA of gene expression in liverworts (Marchantiophyta), representing one of the earliest diverging land plant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
(78 reference statements)
0
27
0
Order By: Relevance
“…Similar assays conducted using Marchantia callus cells (Ghosh et al, 2016a) indicated that overexpression of MpPYL1 cDNA enhanced proEm-GUS and pro4xABRE-GUS expression (Supplemental Fig. S3, A and B).…”
Section: Identification Of Pyr/pyl/rcar-related Genes In M Polymorphamentioning
confidence: 64%
See 2 more Smart Citations
“…Similar assays conducted using Marchantia callus cells (Ghosh et al, 2016a) indicated that overexpression of MpPYL1 cDNA enhanced proEm-GUS and pro4xABRE-GUS expression (Supplemental Fig. S3, A and B).…”
Section: Identification Of Pyr/pyl/rcar-related Genes In M Polymorphamentioning
confidence: 64%
“…We previously showed that ABA-induced gene expression in M. polymorpha is dependent on an ABRE as shown for both the wheat Em promoter and endogenous MpDHN1 promoter (Ghosh et al, 2016a). ABA-induced gene expression by both promoters was inhibited by overexpression of M. polymorpha ABI1A (MpABI1A) encoding group A PP2C, a negative regulator of ABA signaling (Tougane et al, 2010;Ghosh et al, 2016a). Yeast two-hybrid assays indicated that MpPYL1 interacted with MpABI1A (Supplemental Fig.…”
Section: Important Role Of Pyr/pyl/rcar Receptors In Aba Signaling Inmentioning
confidence: 90%
See 1 more Smart Citation
“…Whether these alternative SnRK2-independent ABA signaling pathways play an adaptively relevant role in stomatal function is yet to be determined. The core SnRK2-centric ABA signaling pathway is highly conserved across land plants with all lineages, including those species without stomata, such as liverworts, displaying functional physiological responses to ABA (Ghosh et al, 2016), RCAR/PYR/PYL ABA receptors present in genomes (Hauser et al, 2011), and functional PP2Cs (Tougane et al, 2010). This highly conserved ABA signaling pathway is known to regulate desiccation tolerance mechanisms (Tougane et al, 2010), spore dormancy, and sex determination in nonseed plants , among other processes.…”
Section: Co-option Of An Ancient and Highly Conserved Aba Signaling Pmentioning
confidence: 99%
“…To test whether Mp C1HDZ expression is regulated by abiotic stress, we performed RT-qPCR analysis under NaCl and ABA treatments at two time-points, including also other members of the same protein family. Unlike the strong induction observed for Mp DHN1 [54], Mp HDZ expression remained unaltered or were slightly reduced under these experimental conditions (Figure S10).…”
Section: Resultsmentioning
confidence: 69%